Soybean Cost-Return Budget in Northeast Kansas - Dhuyvetter, Kevin C. (My University, 1996)
This publication projects a budget that reflects expected income and costs based on typical soybean production practices in northeastern Kansas.
MF570_1996_10
Keywords: MF570; Economics; Crops; MF